Neighborhood market potentials for alcohol use and rates of child abuse and neglect. (23rd November 2022) - Freisthler, Bridget; Kranich, Christiana; Price Wolf, Jennifer; Boyd, Reiko; Gruenewald, Paul J.
Abstract: Background: Alcohol use can lead to child abuse and neglect even if the person using alcohol does not use heavily. Yet relatively few measures that reflect alcohol use are available at smaller geographic units. We assess whether the estimated level of total alcohol use per capita is related to measures of child abuse and neglect that include substantiated reports of maltreatment, total entries into foster care, and alcohol‐related entries into foster care. Methods: Our sample consists of 326 Census block groups in Sacramento, California over three time points (978 space–time units). Administrative data for substantiations of child abuse and neglect and foster care entries are our outcomes. We create market potentials for alcohol use among 18‐ to 29‐year‐olds as our primary independent variable. Data are analyzed using Bayesian conditionally autoregressive spatio‐temporal models. Results: Higher alcohol use potentials (as measured by total volume per capita of 18‐ to 29‐year olds) are related to more children entering foster care due to drinking‐related concerns by a parent or caregiver (RR = 1.032, 95% CI = [1.013, 1.051]), but not total substantiations for foster care entries. Neighborhoods with higher total volume of alcohol per 18‐ to 29‐year‐olds had more foster care entries when we used number of substantiations as the denominator (RR = 1.012, 95% CI = [1.0001, 1.023]) but were not related to foster care entries with alcohol misuse as a concern as a subset of all foster care entries. Conclusions: Higher estimated volume of alcohol use per capita among young adults (aged 18 to 29) was related to more children entering foster care due to alcohol‐related concerns. Reducing alcohol supply in alcohol outlets, specifically through off‐premise establishments, might reduce rates for all entries into foster care or other out‐of‐home placement and substantiated child abuse and neglect. Abstract : Neighborhoods with higher estimated volume of alcohol use per capita among young adults 18–29 had more children entering foster care due to parent alcohol misuse. Reducing alcohol supply in alcohol outlets, specifically through off‐premise establishments (e.g., liquor, grocery, or convenience stores), could reduce number of children entering foster care, or other out‐of‐home placements due to child abuse and neglect. The figure shows the relative risk of child abuse and neglect due to volume of alcohol use per capita.